Rethinking teaching readiness: how self-regulated learning transforms prior knowledge and pedagogical competence in early childhood education - Anggarda Paramita Muji; Farida Mayar; Serli Marlina (Education and Social Sciences Review, 2026)
This study addresses a critical gap in teacher education literature concerning how knowledge is transformed into teaching readiness. Although prior knowledge and pedagogical content knowledge (PCK) are widely recognized as essential, the mechanisms linking them to professional readiness remain underexplored. This study proposes self-regulated learning (SRL) as a transformative mechanism connecting knowledge and teaching readiness. A quantitative explanatory design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed, involving 199 early childhood teacher education students in Indonesia. The results show that prior knowledge has the strongest effect on SRL (β = 0.497, t = 7.644), while PCK exerts a substantial direct effect on teaching readiness (β = 0.406, t = 5.000). SRL significantly influences teaching readiness (β = 0.240, t = 2.683) and partially mediates the effects of prior knowledge (β = 0.119, t = 2.659) and PCK (β = 0.107, t = 2.306). These findings indicate that teaching readiness emerges through self-regulatory processes rather than direct knowledge acquisition. This study offers a novel mechanism-based perspective by positioning SRL as a central process in transforming knowledge into professional competence.